The Complementary Role of Motor Imagery on VO2max and Lactate in Professional Football Players with Grade II Ankle Sprains During the Return-to-Play Period - George Plakoutsis; Elias Tsepis; Konstantinos Fousekis; Anna Christakou; Maria Papandreou (Applied Sciences)
Ankle sprains are considered to be the most common musculoskeletal lower limb injury, accounting for a high percentage of all sport injuries in football. Motor imagery (MI) has been widely used for sports performance optimization purposes, suggesting that athletes’ ability to reenact a motor action can improve sports performance and rehabilitation. The aim of the present study was to explore the role of MI as an adjunct intervention in VO2max and lactate in football players with Grade II ankle sprains during the return-to-play period. Fifty-eight professional football players were randomly divided into two groups: first, the MI (n = 29) and second, the placebo (n = 29). The MI group received recorded MI instructions, whereas the placebo group received only relaxation instructions. A one-way ANOVA revealed statistically significant results within the first 4 weeks following the interventions in both groups. Additionally, a t-test showed statistically significant differences between the two groups in VO2max (t = −6.04, p = 0.000, two-tailed, p < 0.05) and lactate (t = 4.33, p = 0.000, two-tailed, p < 0.05). Further research across various sports is needed to better understand the role of MI in the return-to-play period, particularly regarding injury management and sports performance.